Analysis of Blast Fragmentation Results of the Top Air Decking Method in Coal Mines - Adnan Allama (Journal of Information System, Technology and Engineering, 2023)
This research aims to find out what influences the results of blasting fragmentation in the top air decking method. The method used in this research is a quantitative method. The data collection techniques used in this research came from literature studies and field data collection. Processing data analysis is carried out by considering several factors, such as rock characteristics, fragmentation results, and digging time results. After analysis, it can be seen that the design for determining the ADF, ADL, and stemming values is adjusted to the hole depth and PF used so that the fragmentation and digging time obtained are better in order to increase production activities. Based on the research results, it was found that the factors that influence the fragmentation results from top air deck blasting are the powder factor, blasting geometry (burden and spacing), air deck length (ADL), stemming depth, and wet hole conditions. The greater the PF value used, the smaller the fragmentation resulting from blasting and vice versa. The greater the ADL value used, the stemming depth will decrease and there will be potential for stemming injection and producing boulders. More holes in wet conditions will potentially result in greater fragmentation as well. The optimal ADF value to use is 0.3. With an ADF value of 0.3, the ADL used is 0.4–1.47 meters, resulting in better fragmentation. The previous boulder percentage of 18% changed to 7% and the previous digging time of 11.87 seconds changed to 10.57 seconds.